2017
DOI: 10.1093/jat/bkx088
|View full text |Cite
|
Sign up to set email alerts
|

Identification of 5-Fluoro ADB in Human Whole Blood in Four Death Cases

Abstract: Four deaths that seemed to have been caused by a designer drug occurred within a 3-week period in Sendai, Japan. In each case, the decedent possessed the same sachet, labeled "Heart Shot BLACK", which contained a dried plant material with an aromatic scent. It was revealed in our analysis that the product contained a synthetic cannabinoid receptor agonist, 5-fluoro ADB (methyl 2-[1-(5-fluoropentyl)-1H-indazole-3-carboxamide]-3,3-dimethylbutanoate, also known as 5-fluoro MDMB-PINACA), which is now classified as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 13 publications
2
20
1
Order By: Relevance
“…There was no sample where only parent 5F‐ADB was detected. The low blood concentration of 5F‐ADB and AMB‐FUBINACA are consistent with reports where median concentration of related parent SCs in blood was at or below 1 ng/mL . 5F‐ADB was also detected in 70 post‐mortem blood samples at concentrations between 0.10 and 1.55 ng/mL, with a mean of 0.40 ng/mL …”
Section: Resultssupporting
confidence: 85%
“…There was no sample where only parent 5F‐ADB was detected. The low blood concentration of 5F‐ADB and AMB‐FUBINACA are consistent with reports where median concentration of related parent SCs in blood was at or below 1 ng/mL . 5F‐ADB was also detected in 70 post‐mortem blood samples at concentrations between 0.10 and 1.55 ng/mL, with a mean of 0.40 ng/mL …”
Section: Resultssupporting
confidence: 85%
“…Sample preparation and extraction procedures varied widely: liquid-liquid extraction was the most frequently used, though solid-phase extraction (24,44,47,53) and QuEChERS dispersive solid-phase extraction (29,30,35,50) were also reported. Only in a minority of the cases, the standard addition method was employed for quantification (19,23,28,30).…”
Section: Analytical Issuesmentioning
confidence: 99%
“…Atherosclerotic disease and other cardiac abnormalities, such as cardiomegaly and dilatative cardiomyopathy, pose an additional challenge to the assessment of the role of SCRAs in death cases (50,61). In fact, drugs can either exacerbate a preexisting condition, or be considered an irrelevant finding (33).…”
Section: Cause and Mechanism Of Death Tssmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, hydroxypentyl metabolites detected from metabolism experiments with pooled human liver microsomes were also detected in urine samples from two individuals who had been suspected of consuming AB-PINACA , demonstrating that these metabolic products occur in humans. 5F-ADB/5F-MDMB-PINACA, which was implicated in four deaths in Japan of people who had been in possession of a product called "Heart Shock BLACK" (Usui et al, 2018) and others (Hasegawa et al, 2015;Kusano et al, 2018), can also be metabolized to form hydroxylated metabolites, including at the 5 position of the pentyl chain (Barcelo et al, 2017). Metabolism of other synthetic cannabinoids, including AMB, 5F-AMB (Andersson et al, 2016), and EG-018 (Mogler et al, 2018), have been reported to lead to hydroxypentyl metabolites.…”
Section: Introductionmentioning
confidence: 99%